Perencanaan Dan Pengelolaan Keuangan UMKM (Home Industri) Pada Keluarga Ibu Rumah Tangga - Diana, Fina; Rustam, Andi Rustam; Hala, Yusriadi; Solissa, Ferdinando; Astuty, Putu Anggreyani Widya (ADPERTISI, 2023)
Bowong Cindea Village is one of the villages located in Bungoro District, Pangkajene and Islands Regency. Community Service Activities (PKM) is one of the realizations of the tridharma of higher education organized by ADPERTISI in collaboration with the Pangkep Regency Government, aimed at providing solutions to real problems that exist in The community in Bowong Cindea Village, Bungoro District, Pangkep Regency is mainly housewives who have small businesses (home industries). The benefit of this activity is that this PKM activity encourages lecturers who are members of the ADPERTISI organization to interact directly with residents in Pangkep Regency. especially in Bowong Cindea Village in socializing the importance of financial planning and management for their small businesses in improving family welfare. The implementation of Community Service activities is carried out using lecture, tutorial and discussion methods. The PKM activity was attended by the Head of Bowong Cindea Village along with Bowong Cindea Village staff, the Chairperson of the PKK movement. The people of Bowong Cindea Village, especially housewives who have home businesses (hme industry). The presenter provides answers: For processing halal labels/Halal Labels, you must meet administrative requirements such as Business Identification Number (NIB), KTP, NPWP and can be submitted online on the BPJPH page (the body that administers halal product guarantees). Apart from that, there are several institutions that can bridge MSMEs to process Halal Permits